T-tubule remodelling disturbs localised β2-adrenergic signalling in rat ventricular myocyte during the progression of heart failure - Schobesberger,S; Wright,P; Tokar,S; Bhargava,A; Mansfield,C; Glukhov,AV; Poulet,C; Buzuk,A; Monszpart,A; Sikkel,M; Harding,SE; Nikolaev,VO; et al. (Cardiovascular Research, 2017)
AimsCardiomyocyte β2-adrenergic receptor (β2AR) cyclic adenosine monophosphate (cAMP) signalling is regulated by the receptors’ subcellular location within transverse tubules (T-tubules), via interaction with structural and regulatory proteins, which form a signalosome. In chronic heart failure (HF), β2ARs redistribute from T-tubules to the cell surface, which disrupts functional signalosomes and leads to diffuse cAMP signalling. However, the functional consequences of structural changes upon β2AR-cAMP signalling during progression from hypertrophy to advanced HF are unknown.Methods and resultsRat left ventricular myocytes were isolated at 4-, 8-, and 16-week post-myocardial infarction (MI), β2ARs were stimulated either via whole-cell perfusion or locally through the nanopipette of the scanning ion conductance microscope. cAMP release was measured via a Förster Resonance Energy Transfer-based sensor Epac2-camps. Confocal imaging of di-8-ANNEPS-stained cells and immunoblotting were used to determine structural alterations. At 4-week post-MI, T-tubule regularity, density and junctophilin-2 (JPH2) expression were significantly decreased. The amplitude of local β2AR-mediated cAMP in T-tubules was reduced and cAMP diffused throughout the cytosol instead of being locally confined. This was accompanied by partial caveolin-3 (Cav-3) dissociation from the membrane. At 8-week post-MI, the β2AR-mediated cAMP response was observed at the T-tubules and the sarcolemma (crest). Finally, at 16-week post-MI, the whole cell β2AR-mediated cAMP signal was depressed due to adenylate cyclase dysfunction, while overall Cav-3 levels were significantly increased and a substantial portion of Cav-3 dissociated into the cytosol. Overexpression of JPH2 in failing cells in vitro or AAV9.SERCA2a gene therapy in vivo did not improve β2AR-mediated signal compartmentation or reduce cAMP diffusion.ConclusionAlthough changes in T-tubule structure